2002
DOI: 10.1128/aac.46.11.3654-3656.2002
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in Cefepime Titration from Human Plasma: Plasma- and Temperature-Related Drug Degradation In Vitro

Abstract: While developing a high-pressure liquid chromatography assay for cefepime in plasma, we observed significant drug degradation at 20 and 37°C but not at 4°C. This plasma-related degradation persisted after protein removal. This warrants caution regarding cefepime assays for pharmacokinetic and pharmacodynamic studies of cefepime in vitro and in vivo.While a high-pressure liquid chromatography (HPLC) method to measure levels of cefepime in plasma was being validated, significant plasma-dependent and temperature-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Cherti et al [25] and Elkhaïlï et al [26] described important degradation of aqueous extracts originating from plasma after sample pre-treatment in cefepime. Bugnon et al [28] also showed that cefepime degradation in plasma samples at room temperature occurred in spite of prior plasma deproteinization and recommended to maintain samples at 4 • C. The stability of samples used for pharmacokinetic analyses is guaranteed with our HPLC method for the period of time described above.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Cherti et al [25] and Elkhaïlï et al [26] described important degradation of aqueous extracts originating from plasma after sample pre-treatment in cefepime. Bugnon et al [28] also showed that cefepime degradation in plasma samples at room temperature occurred in spite of prior plasma deproteinization and recommended to maintain samples at 4 • C. The stability of samples used for pharmacokinetic analyses is guaranteed with our HPLC method for the period of time described above.…”
Section: Discussionmentioning
confidence: 94%
“…Although other HPLC methods have been published in the literature for ceftazidime [20][21][22][23] and cefepime [24][25][26][27] determination in different fluids, only a few of the works mentioned above provide data about drugs' stability [22,25,26,28]. Our work includes a complete stability study because stability assessment is considered a fundamental parameter for the validation of bioanalytical methods [16,29], and is critical for proper interpretation of analytical results [13].…”
Section: Discussionmentioning
confidence: 97%
“…Data gathered thus far suggest that TDM can help to minimize the risk of major adverse reactions and to increase drug safety on an individual basis . Analytical methods for monitoring cefepime in biosamples include bioassays , HPLC with UV detection , LC–MS , and MEKC . They should be capable of accurately monitoring cefepime levels in the range of 1 to 50 μg/mL .…”
Section: Introductionmentioning
confidence: 99%
“…Tubes were centrifuged at 4°C within 1 h and stored at Ϫ80°C until analysis. Cefepime plasma concentrations were measured by a UV high-performance liquid chromatography method validated according to international guidelines (5). The analytical range was 0.25 to 200 mg/liter, and the intrarun/interrun accuracy and coefficient of variation were Ͼ95% and Ͻ10%, respectively.…”
Section: Settingmentioning
confidence: 99%